Changes in Amplitude-integrated Electroencephalograms in Piglets During Selective Mild Head Cooling After Hypoxia-ischemia - Ji-Mei Wang; Guo-Fu Zhang; Wen-Hao Zhou; Ze-Dong Jiang; Xiao-Mei Shao (Pediatrics and Neonatology)
Amplitude-integrated electroencephalogram (aEEG) is a simplified, alternative means of monitoring cerebral function and may be more useful clinically in some situations than conventional EEG. The aim of this study is to evaluate newborn piglets as an animal model to examine the effect of selective mild head cooling (HC) on aEEG after hypoxia-ischemia (HI). Methods: Thirty-four piglets were randomly allocated to the following treatment groups: normothermic control group (NC, n = 7), selective HC control group (HC, n = 9), normothermic HI group (NHI, n = 9), and selective HC HI group (SHC-HI, n = 9). HI was induced by temporary occlusion of both carotid arteries and simultaneous reduction of the concentration of inspired oxygen to 6% for 30 minutes. Mild hypothermia (35°C) was induced after HI using a HC cap and was maintained for 24 hours. Changes in aEEG were monitored for 6 days after these treatments and the incidence of abnormalities analyzed. Physiological parameters were also measured during this period. Results: In the two HI groups, animals exhibited severely abnormal aEEGs [continuous low voltage (CLV), burst-suppression, or flat tracing (FT)] 20 minutes after the beginning of HI. At 2 hours, the aEEG returned to normal in most of these animals. From 12 hours to 6 days, all animals in the NHI group exhibited severely abnormal aEEGs. Fewer animals in the SHC-HI group exhibited severe abnormal aEEGs during this time period, and four out of nine (44.4%) animals had continuous normal voltage (CNV) at 6 days. Conclusions: Selective mild HC decreases the incidence of severe abnormal aEEGs at late times after HI in newborn piglets.